Heparanase modulates the prognosis and development of BRAF V600E-mutant colorectal cancer by regulating AKT/p27Kip1/Cyclin E2 pathway - Mengling Liu; Xiaojing Xu; Ke Peng; Pengcong Hou; Yitao Yuan; Suyao Li; Xun Sun; Zhongyi Shi; Jiayu Zhang; Yu Dong; Qing Liu; Luoyan Ai; et al. (Oncogenesis, 2022)
Abstract BRAF V600E-mutant colorectal cancer (CRC) is a rare subtype of colorectal cancer with poor prognosis. Compelling evidence indicates that the heparanase (HPSE) gene has multiple functions in cancer, however, its role in BRAF V600E-mutant CRC remains elusive. Differentially expressed genes between BRAF V600E-mutant and wild-type patients were explored by analyzing public data from The Cancer Genome Atlas and the Gene Expression Omnibus. Clinical samples of 172 patients with BRAF V600E-mutant CRC diagnosed at Zhongshan Hospital Fudan University were collected. Overall survival was analyzed using Kaplan–Meier curves and Cox regression models. Cell models and xenografts were utilized to investigate the effect of HPSE on tumor proliferation. HPSE was significantly highly expressed in the BRAF V600E-mutant group. High HPSE expression level was independently associated with inferior survival in the BRAF V600E-mutant cohort. HPSE knockdown impeded tumor proliferation of BRAF V600E-mutant CRC cells in vitro and in vivo. Mechanistically, HPSE silencing arrested cell cycle in G0/G1 phase by downregulating Cyclin E2 expression via the AKT/p27Kip1 pathway. These findings support a role for HPSE in promoting BRAF V600E-mutant CRC progression, which suggests it holds great promise as a prognostic biomarker and a potential therapeutic target for the aggressive CRC subtype.